Evolution of Food Innovation in Hospitality and Tourism: An SLR on Local Heritage and Gastronomy Resilience - Intan, Amalia Juliana Monika; Alim, Azmi Kautsar; Widiyanti, Rikantini (Journal of Tourism Sustainability, 2025)
This study systematically reviews the evolution of food innovation in the hospitality and tourism industry, specifically focusing on the intersection of local food heritage, health-conscious consumption, and sustainability. It aims to examine how food innovation serves as a strategic dynamic capability that influences tourist acceptance and contributes to destination resilience in the post-pandemic context. Following the PRISMA guidelines, a Systematic Literature Review (SLR) was conducted using 34 peer-reviewed articles retrieved from the Scopus database (2020–2025). A qualitative thematic synthesis was employed to categorize innovation drivers, implementation mechanisms, and strategic outcomes, analyzed through the theoretical lens of Dynamic Capabilities and Destination Resilience. The findings reveal a paradigm shift from industrial efficiency toward authenticity-oriented and sustainability-driven practices. Two dominant drivers emerge: the revitalization of indigenous food systems and the demand for functional/health-oriented foods. Crucially, the review identifies that these innovations are operationalized through Short Food Supply Chains (SFSCs), which function as mediating capabilities that transform local resources into competitive advantages. This review contributes to hospitality scholarship by proposing a novel "Sustainable Gastronomy Resilience" framework. Unlike previous product-centric studies, this research theoretically positions food innovation as a core strategic asset for regional stability. The findings offer actionable insights for destination managers and practitioners to strengthen resilience through supply chain integration and culinary storytelling.